Road safety inspections: Basic principles - Carlo Polidori (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
Some European Union Directives which were implemented by the various Member States, have established the fundamental guidelines for safety inspections of road infrastructures, according to the principle of the independence of the inspectors with respect to both the owner of the infrastructure and of its manager. This article addresses the practical implementation of the guidelines based on some inspections carried out on motorway sections in Italy.